Sistem Motor Listrik 6 KV Condensate Extraction Pump di PT Indonesia Power PLTU Suralaya (PGU) - Feri Febrian Syah; Endi Permata (Pusat Riset dan Inovasi Nasional, 2023)
In a steam power plant, of course, it has a very important prime mover, namely an electric motor, but electric motors are used in a variety of functions, one of the main roles in this electric motor is as a condensate extraction pump in a steam power plant which functions to push materials for power plant production. Steam power, namely sea water, goes to the generator to become a power plant. The method used is qualitative by using observation techniques, interviews and literature studies. This condensate extraction pump (CEP) electric motor can be operated automatically and manually for routine maintenance and good inspection results.